Health Science Educator Preparation Toward an Industrial Revolution 5.0 Era in Education: A Case Study - Fatimah , Siti (Jurnal Kesehatan Pertiwi, 2024)
Industrial Revolution 5.0 Era is an Era that also affected of education system in Indonesia, which one of the influences is the competence of the educator in using technology and also international language like English while teaching. These realities became a consideration for the educator to improve their quality and services to the student to face 5.0 Era. Based on that consideration, this study investigated the educator (lecturer) preparation toward an Industrial Revolution 5.0 Era in Education. This study applied descriptive method, which used qualitative as the approach. Questionnaire, observation, and interviews were used as data collection. The questionnaires were spread to 22 lecturers in Polytechnic of Health Science Bhakti Pertiwi Husada Cirebon (BPH), Indonesia. The research reveals that the educators are quite well prepared; it also shows that the lecturers have well preparation in creating learning target, using the teaching strategies, and doing the learning evaluation effectively. The other factor that also influence the lecturer preparation are BPH always improve the educator knowledge by involve them in workshops or seminars. The research also shows that lecturer needs to learn English Language as high as their needs to improve the students’ qualities. The recommendation is to conduct an optional course on English for Professional Purposes.